Ponto de entrega voluntária de resíduos sólidos na cidade de Manaus: uma proposta de avaliação - Nascimento, Leonardo D'Avila do (Brasil, 2024)
The increase in consumption, mainly through internet purchases, online delivery orders, among others, results in products with different packaging and wrapping, in addition, the acceleration of planned obsolescence (noticeable in the short launch time between a version smartphone and another “better”) exemplify one of the biggest challenges facing today’s societies: dealing with the management of the volume of urban solid waste. The excessive generation of this waste directly affects sustainable development and compromises the environment. The correct disposal of this waste, its recycling and its return to the production chain is a strong tool in the search to mitigate the effects of this excess consumption. From this perspective, the present work proposed to analyze the voluntary delivery points managed by the public authorities of the city of Manaus, seeking to identify the flow that the waste received by these points travels, as well as the sustainability of the existing model, through secondary data collection and field observations. The results obtained, in addition to demonstrating the current situation of logistics present in the delivery, collection and distribution of waste, managed to demonstrate the current distribution of points throughout the city and the sustainability of the model, pointing out the dispersion of these points in all areas of the city and the participation of the population in this model, but also indicating the need for adjustments, such as: a greater number of voluntary delivery points, improvement of the current structure and educational actions to continually raise awareness among the population.